Diarylquinolines, synthesis pathways and quantitative structure–activity relationship studies leading to the discovery of TMC207. (September 2011) - Guillemont, Jerome; Meyer, Christophe; Poncelet, Alain; Bourdrez, Xavier; Andries, Koen
The emergence of multidrug-resistant strains of Mycobacterium tuberculosis and resistance to current anti-TB drugs call for the discovery and development of new effective anti-TB drugs. TMC207 is the lead candidate of a novel class of antimycobacterial agents, the diarylquinolines, which specifically inhibit mycobacterial ATP synthase and displays high activity against both drug-susceptible and multidrug-resistant strains of Mycobacterium tuberculosis . This article covers both synthesis pathways as well as qualitative and quantitative analyses of the structure–activity relationships of the diarylquinoline series on Mycobacterium smegmatis activity.